Biochemical Pathway of Stress-induced Ethylene - Abeles, A. L. (1972)
Ethylene production from beam and tobacco leaves increased rapidly following the application of toxic compounds such as CuSO(4), Endothal, and ozone. Treatments which increased ethylene evolution also increased the conversion of U-(14)C-methionine into ethylene. Cycloheximide inhibited the production of chemical stress-induced ethylene. These results suggest that ethylene is produced by the same biochemical pathway forming basal ethylene, auxin-induced ethylene, or that produced during the ripening of climacteric fruit.